INFLUENCE OF THE EFFECTIVENESS OF COLLECTIONS OF ECONOMIC LITERATURE, INTEREST IN READING AND LEARNING DISCIPLINES ON LEARNING ACHIEVEMENT: PENGARUH EFEKTIVITAS KOLEKSI LITERATUR EKONOMI, MINAT MEMBACA DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR - Novika Sri Pratiwi (Yayasan Education and Social Center, 2022)
This study aims to analyze the effect of the effectiveness of economic literature collection, reading interest and learning discipline on learning achievement. The method used in this research is a quantitative method. The population in this study were students of the Faculty of Economics, State University of Jakarta, class of 2017 and the sample was 179 students of the Faculty of Economics, State University of Jakarta. The sampling technique is proportional random sampling. The data was collected by distributing questionnaires or questionnaires to 179 students of the Faculty of Economics, State University of Jakarta. The data analysis technique used is path analysis. The results of this study are: 1) The effectiveness of the economic literature collection has an effect of 15.6% on learning achievement, 2) reading interest has an effect of 61.2% on learning achievement, 3) learning discipline has an effect of 14.6% on learning achievement, 4) The effectiveness of the collection of economic literature, reading interest and learning discipline together have an effect of 64.5% and the rest are influenced by other factors